Translation of Fit & Strong! for Middle-Aged and Older Adults: Examining Implementation and Effectiveness of a Lay-Led Model in Central Texas - Ory, Marcia G.; Lee, Shinduk; Zollinger, Alyson; Bhurtyal, Kiran; Jiang, Luohua; Smith, Matthew Lee (Frontiers in Public Health, 2015)
.